(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
Sponges are symbiotic organisms that play a significant role in coastal ecosystems, such as filtering water, decomposing organic material into nutrients, providing shelter for microorganisms, and contributing to sediment stability and binding. This study aims to identify the composition and species diversity of sponges found in seagrass habitats on Panggang Island, Thousand Islands, DKI Jakarta. The research was conducted at three locations using a 50-meter line transect and 11 square transects measuring 0.5 x 0.5 meters along each line. Sponge samples were collected by cutting small pieces from each sponge for spicule analysis. The results indicate that a total of 10 sponge species were recorded across all research locations, dominated by Chondrilla caribensis forma, with sponge density values ranging from 0 to 13 individuals/m². The sponge diversity index on Panggang Island falls within the moderate category, indicating that the distribution of genera within the sponge community is relatively even. Phosphate concentration and current velocity showed a strong positive correlation with sponge density, while temperature exhibited a positive correlation with seagrass density. Conversely, the correlation between sponge density and seagrass density was relatively weak, supporting the findings that these two components do not have a close relationship within the observed ecosystem.